Water and wastewater technology - Hammer, Mark J. , 1957-; Hammer, Mark J. , 1957- (Prentice Hall, 2012)
Overview: The new edition of Water and Wastewater continues its traditional coverage of water processing principles and modern management practices, but now integrates a new emphasis on sustainability throughout. Comprehensive coverage of such topics as: Water processing; Water distribution; Wastewater collection; Conventional and advanced wastewater treatment; Sludge processing. Key and New Features include: Coverage of new technologies; Water supply and water sustainability woven throughout; Coverage of energy reduction opportunities, and other processes important to water sustainability; Extensive use of illustrations to explain concepts and demonstrate modern equipment and facilities; Extensive use of charts, diagrams, and tables to make the mathematics more accessible